Overcoming barriers to maintain hemodialysis adequacy amongst hemodialysis patients in hospital: a best practice implementation project. Issue 3 (9th September 2021) - Tseng, Peng-Lin; Lin, Ni-Ni; Hsu, Li-Ping; Tasi, Yu-Mei; Chen, Bao-Chen; Mu, Pei-Fan
ABSTRACT: Objective: The aim of this evidence implementation project was to identify the barriers and omissions affecting adequacy of hemodialysis and to develop implementable strategies to maintain hemodialysis adequacy among hemodialysis patients with end-stage renal disease. Introduction: Assessing adequacy of hemodialysis and improving quality of life are important issues for patients with end-stage renal disease. However, they are often inadequately addressed, and evidence-based practices are not always followed. Methods: A clinical audit was undertaken using the Joanna Briggs Institute Practical Application of Clinical Evidence System and Getting Research into Practice approaches. Seven audit criteria that represent best practice recommendations for maintaining hemodialysis adequacy among hemodialysis patients were used. A baseline audit was performed, which was followed by the implementation of multiple improvement strategies over 20 weeks and the outcomes finalized using a follow-up audit to determine the change to be implemented in practice. Results: The baseline audit results showed that most audit criteria were less than 77% in practice. The compliance rates for nurses who had received education regarding hemodialysis, checking the prescription order for each patient at each session, and using the prescribed dialyzer for every session were determined to have reached 100% at the follow-up audit. The compliance rates for completion prehemodialysis checks, using a sterile technique when inserting an arteriovenous catheter, matching a blood flow rate with the prescription, and maintaining a blood flow rate throughout the treatment session were found to be 73–95% at the follow-up audit. The most significant finding was the proportion of hemodialysis patients with inadequate urea reduction ratio was reduced from 4.6 to 3.2% after implementation of the best practice approaches. Conclusion: The implementation of institution-specific evidence-based resources brought about immediate improvements in hemodialysis adequacy management and practice. A variety of strategies contributed to the success of this implementation project, such as scenario simulation education, Objective Structured Clinical Examination, the interrelation response system Kahoot, the use of hemodialysis International Organization for Standardization job descriptions, regular weekly audits, and collaboration with physicians when caring for patients during clinical practice.